2020
DOI: 10.5606/tgkdc.dergisi.2020.19610
|View full text |Cite
|
Sign up to set email alerts
|

The association between pneumothorax onset and meteorological parameters and air pollution

Abstract: Background: The aim of this study was to investigate the possible relation of meteorological parameters and air pollutant particle concentrations with the incidence of spontaneous pneumothorax in the Bolu region of Turkey. Methods: Between January 2015 and February 2019, a total of 200 patients (175 males, 25 females; mean age 42.5±19.9 years, range, 10 to 88 years) with spontaneous pneumothorax were retrospectively analyzed. For each day, standard weather parameters including daily average temperature, relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Özpolat et al 16 showed that PSP was associated with low temperature but noted that this might be a cofactor rather than having a direct effect. In another study of 200 patients, Yaksi et al 19 also found that a reduction in temperature was significantly associated with the development of PSP. Sahinoglu et al 20 reported that temperature higher than 15°C may contribute to the development of PSP and that when compared with blood group, people with blood group O were more resistant to temperature changes.…”
Section: Authors' Contributionsmentioning
confidence: 90%
“…Özpolat et al 16 showed that PSP was associated with low temperature but noted that this might be a cofactor rather than having a direct effect. In another study of 200 patients, Yaksi et al 19 also found that a reduction in temperature was significantly associated with the development of PSP. Sahinoglu et al 20 reported that temperature higher than 15°C may contribute to the development of PSP and that when compared with blood group, people with blood group O were more resistant to temperature changes.…”
Section: Authors' Contributionsmentioning
confidence: 90%